INVESTIGATION OF THE ACCURACY PARTIAL-FLOW CONTROL SYSTEMS FOR PARTICULATE EMISSIONS FROM DIESEL EXHAUST GASES: Array - Polivyanchuk, A. (Municipal economy of cities. Series: «Economy science», 2019)
The work is devoted to solving the problem of ensuring the required accuracy of frequent-flow mini- and microtunnels - compact systems for controlling mass emissions of particulate matter from diesel engines, which arises due to the difference in temperature conditions of sample preparation in these tunnels and the reference measurement system - full-flow tunnel. According to the results of the analysis of regulatory documents - UNECE Rules R-49, R-96, international standard ISO 8178 and others, international and domestic experience in the use of dilution tunnels, it was established: technical characteristics and operating conditions of reference full-flow and part-flow tunnels, empirical dependencies characterizing the degree the influence of the sample temperature of diluted exhaust gases in the tunnel on the accuracy of measurements of mass emissions of particulate matter at various diesel operating modes. Mathematical models have been developed to determine: sample temperatures in tunnels of various types, the resulting measurement error of the average operational emission of particulate matter - PM index, taking into account the influence of sample temperature in the tunnel on the accuracy of PM measurements. Based on the results of tests of 1Ч12/14 and 4ЧН12/14 diesel engines according to the ESC cycle and developed mathematical models, computational studies were carried out to assess the impact on the accuracy of the minitunnel and microtunnel with diameters of 10 cm and 3 cm, respectively, of the temperature conditions of sample preparation, which were compared with a reference system with diameter, 46 cm. The research results proved the feasibility of controlling the temperature of the sample in the microtunnel to eliminate significant methodological errors in the measurement of PM, which are -1.6 ... -1.7%. In a minitunnel, the corresponding errors are not significant and equal to -0.3 ... -0.4%. Since the thermal conditions for diluting the exhaust gases in the minitunnel and the reference system are approximately equal, there is no need to control the sample temperature in this system.